A Genre Analysis of Research Article Abstracts in Linguistics and Engineering: a Cross Disciplinary Study Based on a Contrastive Analysis of Micro Structures - Andrii Galaidin (Language, Culture, Politics)
The signicance of a research article abstract has recently turned the focus of linguistics on the Genre analysis of abstract articles. Taking into account this wide research topic, this study aims at investigating the micro structures in the linguistics and engineering abstracts. In the previous studies, this comparison has not been addressed by the researches, hence the present study aims to ll in the gap. The corpus contained 30 abstracts, 15 of linguistics and 15 of engineering. The micro analysis was carried out on the basis of Swales and Feak's (2009) model. The results revealed that there was no very signicant dierence between the linguistics and engineering abstracts at the micro level. This study is deemed to be benecial for the researchers as it provides a framework of analyzing two dierent disciplines in terms of their abstracts.